2017
DOI: 10.3390/molecules22111963
|View full text |Cite
|
Sign up to set email alerts
|

Design, Recombinant Fusion Expression and Biological Evaluation of Vasoactive Intestinal Peptide Analogue as Novel Antimicrobial Agent

Abstract: Antimicrobial peptides represent an emerging category of therapeutic agents with remarkable structural and functional diversity. Modified vasoactive intestinal peptide (VIP) (VIP analogue 8 with amino acid sequence “FTANYTRLRRQLAVRRYLAAILGRR”) without haemolytic activity and cytotoxicity displayed enhanced antimicrobial activities against Staphylococcus aureus (S. aureus) ATCC 25923 and Escherichia coli (E. coli) ATCC 25922 than parent VIP even in the presence of 180 mM NaCl or 50 mM MgCl2, or in the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The environmental pH can influence the activity and amphipathic structure of the AMPs as well as their interaction with the cell membrane of micro‐organisms (Xu et al., ). Our results also revealed pH‐dependent activity of MCH‐AMP1 (Figure b), which was seen to become stable within the narrow pH range of 7–11.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental pH can influence the activity and amphipathic structure of the AMPs as well as their interaction with the cell membrane of micro‐organisms (Xu et al., ). Our results also revealed pH‐dependent activity of MCH‐AMP1 (Figure b), which was seen to become stable within the narrow pH range of 7–11.…”
Section: Discussionmentioning
confidence: 99%
“…However, some disadvantages limit its practical application. Therefore, in our previous research, we designed a VIP analogue, via amino residue substitution (Asp 3 →Lys 3 , Asp 8 →Lys 8 ), with safety, favorable stability and improved antimicrobial activities, and established a green, efficient and low-cost production technology via E. coli -recombinant expression system[ 21 ]. However, it remains to be elucidated whether the molecular modification and recombinant generation affect its anti-inflammatory activity or not.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, Gong et al and Xu et al reported that AMPs maintain their antimicrobial activities as fusion proteins. 16,17 Because AMPs maintain membrane activity in their fusion forms, they could be used to decorate membranes after fusion expression with proteins of interest. Ib-AMP4, which possesses two disulfide bonds, occurs in Impatiens balsamina and exhibits broad antimicrobial activity against plant pathogens.…”
Section: ■ Introductionmentioning
confidence: 88%